Analysis of the Application of PSAK No.45 Concerning Financial Reporting of Non-Profit Organizations in Achieving Transparency and Accountability (Case Study of At-Taqwa Great Mosque, Miftahul Jannah Mosque, Annasuha Mosque, Baitul Atieq Mosque, and Bengk - Deva Asmarita; Wagini Wagini; Rina Trisna Yanti (Penerbit Jurnal Indonesia, 2022)
This study aims to analyze the application of PSAK 45 concerning financial reporting of non-profit organizations in achieving transparency and accountability (Case Study at At-Taqwa Great Mosque, Miftahul Jannah Mosque, Annasuha Mosque, Baitul Atieq Mosque, and An-Nur Mosque in Bengkulu City). The data analysis used is descriptive comparative, namely a research method that compares a theory that applies to events that occur in the field. The results of this study indicate that these mosques in particular have not made financial reports in accordance with PASK No. 45, but in the financial reports, At-Taqwa Great Mosque has implemented PSAK 45 even though it is only 55.55%, Miftahul Jannah Mosque, Annasuha Mosque, Baitul Atieq Mosque and Majid An-Nur have implemented PSAK 45 even though it is only 50%. While for the transparency and accountability as a whole the five mosques have been transparent and accountable in their financial reports.